2021
DOI: 10.1016/j.ajo.2021.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline Characteristics on Geographic Atrophy Progression in the FILLY Trial Evaluating the Complement C3 Inhibitor Pegcetacoplan

Abstract: To evaluate the effect of select baseline characteristics on geographic atrophy (GA) progression in eyes receiving intravitreal pegcetacoplan or sham. • DESIGN: Phase 2 multicenter, randomized, singlemasked, sham-controlled trial. • METHODS: Patients with GA received 15 mg pegcetacoplan monthly or every other month (EOM), or sham injection monthly or EOM for 12 months. Primary efficacy endpoint was change in GA lesion size (square root) from baseline. Post hoc analysis evaluated the effects of age; gender; les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 23 publications
1
18
0
3
Order By: Relevance
“…This C3 inhibitor, locally administrated via intravitreal injection, has proven to mitigate GA enlargement versus placebo treatment [ 153 ]. The FILLY study found that Pegcetacoplan treatment monthly resulted in a 29% of reduction of atrophic progression compared to sham controls, even after controlling for confounding factors [ 154 ]. To confirm APL-2 success, two phase 3 studies have completed enrolment (OAKS NCT03525613 and DERBY NCT03525600) and will define its efficacy and safety profile as a GA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This C3 inhibitor, locally administrated via intravitreal injection, has proven to mitigate GA enlargement versus placebo treatment [ 153 ]. The FILLY study found that Pegcetacoplan treatment monthly resulted in a 29% of reduction of atrophic progression compared to sham controls, even after controlling for confounding factors [ 154 ]. To confirm APL-2 success, two phase 3 studies have completed enrolment (OAKS NCT03525613 and DERBY NCT03525600) and will define its efficacy and safety profile as a GA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 47 prespecified genetic variants associated with AMD risk were not associated with GA lesion growth rate or response to treatment. In a post hoc analysis, there was a persistent effect of pegcetacoplan on GA growth even after controlling for known risk factors of GA in AMD, extrafoveal lesions and larger low luminance deficits [12]. In summary, the FILLY trial found that treatment of GA patients with intravitreal injections of pegcetacoplan was associated with a reduction in the rate of GA lesion growth, even after controlling for confounding factors.…”
Section: C3 Inhibitionmentioning
confidence: 86%
“…Nevertheless, they were associated with an unexpected increased incidence of new-onset neovascularization, identified to be dosedependent. The conversion from a nonexudative MNV to exudative MNV in these eyes has been suggested to be the main cause, and it may have an immunologic basis, but further study of these hypotheses is being pursued in an ongoing global phase 3 study [102][103][104]. Second, NGM621 is a humanized IgG1 monoclonal antibody engineered to potently inhibit the activity of C3, which was safe and well-tolerated in phase I trials [88].…”
Section: The Role Of Complementmentioning
confidence: 99%